Efektivitas Pengelolaan Alokasi Dana Desa dalam Pembangunan Infrastruktur Kampung Medang Ara Kacamatan Karang Baru Kabupaten Aceh Tamiang - Benny Syahputra Nasution; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2023)
This study aims to analyze the effectiveness and inhibiting factors in managing village fund allocations in infrastructure development in Kampung Medang Ara, Karang Baru District, Aceh Tamiang Regency. This study uses a qualitative method with a descriptive approach. Data collection was obtained from Secondary Data consisting of: history of establishment, organizational structure, vision and mission, and goals to be achieved; primary data, obtained from interviewing informants in the field. To analyze effectiveness, Edward III's theory was used, among others: namely communication, resources, disposition and bureaucratic structure. The results of the study found that in terms of communication between employees and village government officials it was good, but increased socialization with the community. In infrastructure development, human and material resources are inadequate due to a shortage of executive staff, as well as facilities and infrastructure. Village officials are quite committed and responsible for implementing the road infrastructure development program in accordance with the procedures that have been prepared. The inhibiting factors are inadequate human resources, very few village government officials and a lack of supporting facilities and infrastructure. The use of village fund allocation budgets can be resolved properly but the lack of information transparency causes a lack of community participation so that the target of allocating funds has not been achieved.